0183 Daily sleep predicts adolescents' next-day psychomotor vigilance, sleepiness, and fatigue: Ecological momentary assessment across 28 days of school and vacation. (25th May 2022) - Shen, Lin; Sletten, Tracey; Wiley, Joshua; Bei, Bei
Abstract: Introduction: Few studies have examined the associations between daily sleep and daytime functioning in adolescents during naturalistically-occurring constrained (school term) and unconstrained (vacation) sleep opportunities. Methods: Adolescents (n = 205; 54.1% females, age M ± SD = 16.9 ± 0.87 years) completed daily measures of sleep and daytime functioning over 28 continuous days (2-week school, and the subsequent 2-week vacation). Total sleep time (TST) and sleep efficiency (SE) were measured using actigraphy and sleep diary. Participants self-reported sleepiness and fatigue every morning and afternoon, and completed the brief, 3.2-minute psychomotor vigilance task (PVT; Joggle Research) on an iPad every afternoon. Using cross-lagged multilevel models, daily TST and SE were examined as predictors of next-day sleepiness, fatigue, and PVT performance. The associations did not differ between school and vacation. The non-significant interaction terms were dropped, and school/vacation status was maintained as a covariate. Previous-day outcome, day of the week, study day, school/vacation and sociodemographics were adjusted. Between-person associations (differences between individuals) and within-person associations (daily deviations from individual's own mean capturing whether nights with longer- or better-than-average TST or SE respectively, relative to the individual's average TST/SE, predict next-day outcomes) were tested simultaneously. Results: Adolescents performed better on the PVT (faster reaction time and fewer lapses) following nights with longer-than-average TST (actigraphy and diary, p-values ≤ .044). Longer-than-average TST (actigraphy and diary) and higher diary SE also predicted lower self-reported sleepiness the next day (morning and afternoon, p-values ≤ .002). Similarly, longer-than-average TST and higher-than-average SE predicted lower self-reported fatigue the next day (morning and afternoon, all p-values ≤ .032). Compared to the vacation, school term was associated with higher self-reported fatigue in the morning and afternoon (p-values ≤ .014), but not higher sleepiness or poorer PVT performance. Conclusion: Fluctuations in daily sleep were associated with adolescents' next-day functioning. Importantly, longer- and better-than-average sleep consistently predicted better daytime functioning the next day. Findings were consistent across objective sustained attention and self-reported sleepiness and fatigue, highlighting the short-term effects of sleep restriction on adolescents' daytime functioning. Protecting adolescents' sleep duration and promoting good quality sleep on a daily basis could support optimal daytime functioning. Support (If Any): Dr Shen was supported by the Monash International Postgraduate Research Scholarship and Monash Graduate Scholarship.